Accessing information and adapting to the role of care partner for stroke survivors with aphasia during the early Covid-19 pandemic. Issue 6 (3rd June 2023) - Shafer, Jennifer S.; Haley, Katarina L.; Jacks, Adam
ABSTRACT: Background: Spouses, family members, and close friends of stroke survivors with aphasia are often inadequately prepared to transition into the role of care partner and are consequently at risk for third-party disability. Timely, appropriate informational support may help to mitigate negative effects of caring for someone with aphasia. Aims: To explore how 11 care partners accessed information and adapted to the caregiver role at different phases of recovery during the early Covid-19 pandemic. Methods and Procedures: Care partners of stroke survivors with aphasia participated in up to five individual semi-structured interviews while their loved one was in acute care through six months post-hospital discharge. The interviews were audio-recorded and transcribed. Transcripts were analysed using a descriptive coding process. Codes were grouped together into categories, and themes were identified from observed patterns in the data. Outcomes and Results: There were 11 relevant key themes, including how care partners learn about stroke and aphasia (or not), receive information about their loved one, find alternative ways to communicate, prepare for the unknown, long for some type of check-in, desire care coordination, appreciate family support, and adjust to living with aphasia in the long-term. Conclusions: The Covid-19 pandemic highlighted inconsistencies in care partner involvement during stroke rehabilitation. Families navigated stroke and aphasia recovery with varying information from the healthcare team and the pandemic impacted therapy coordination, family support, and access to respite care. Our work highlights several opportunities for improvement in care partner inclusion and indicates a need to develop tailored interventions for timely informational support.